Acts Of Omission Dan Tanggung Jawab Negara Dalam Perlindungan HAM Internasional - Layn, Mirna Waty; Peilouw, Johanis Steny Franco; Riry, Welly Angela (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction: If we look at the cases of violations of human rights in the United States where youths aged 18 years used firearms to commit acts of murder, it is therefore clear that these violations of human rights must still be accounted for in accordance with the provisions that apply to the International Law Commission and the International Covenant on Civil and Political Rights (ICCPR).Purposes of the Research: This writing aims to examine and find out the arrangements regarding Acts Of Omission in international human rights instruments and state accountability in Acts Of Omission as a form of human rights protection.Methods of the Research: The type of research used in this paper is normative legal research. As for answering the problems in this study, the authors use three approaches to the problem, namely the statutory approach (statute approach), dan conceptual approach (conceptual approach). The procedure for collecting legal materials carried out by the author is by searching for and collecting laws and regulations related to the legal issues at hand. Legislation in this case includes both legislation and regulation. Analysis of legal material uses qualitative methods, namely studies related to legal norms contained in international law legislation and legal norms that exist in society.Results of the Research: The results of this study show that the provisions concerning acts of omission in international human rights instruments are contained in the Universal Declaration of Human Rights. The protection provided by the state is part of respect for human dignity. The Universal Declaration of Human Rights proclaimed a common standard of achieving well-being for all people and all nations. This declaration includes all rights under civil-political rights (ICCPR) as well as economic, social and cultural rights (ICESCR).